Re-conceptualizing innovative incubation models for agribusiness SMEs growth in China using resource-based perspectives - Yongming, Chen; Latip, Malisah; Sharkawi, Ismawati; Mat Jusoh, Nurul Hidayu (Iquz Galaxy Publisher, 2026)
Business incubation is a crucial mechanism for supporting the development of small and medium-sized enterprises (SMEs), particularly in emerging economies such as China. In the context of agribusiness, incubation plays an increasingly vital role in enhancing innovation, market access, and sustainability among agricultural entrepreneurs and food-based SMEs. This study develops a conceptual framework by integrating the Resource-Based View (RBV), Dynamic Capabilities (DC), and the Natural Resource-Based View (NRBV) to explain how incubator resources, including financial, human, technical, and network support, shape the outcomes of agribusiness SMEs through capability building and sustainability integration. The framework emphasizes the intention of agribusiness SMEs to form a long-term partnership with incubators as the focal dependent variable. This intention reflects their willingness for continuous collaboration, recognition of the incubator as a strategic partner in agrifood development, commitment to innovation, and confidence in the sustainable value of incubation services. By positioning partnership intention as the proximate outcome, the study highlights how effective resource allocation and capability development within agribusiness incubators can translate into enduring collaboration, which in turn creates a pathway to SME growth, competitiveness, and sustainable agricultural advancement. The paper contributes to incubation theory by integrating RBV, DC, and NRBV into a dynamic model while offering practical guidance for designing incubation strategies that strengthen agricultural entrepreneurship and foster sustainable partnerships in China’s agribusiness sector.